Dual role of KRT17: development of papillary renal cell tumor and progression of conventional renal cell carcinoma - Sarlós, Donát Péter; Kovacs, Gyula (Journal of cancer, 2019)
Expression of KRT17 has been described in multi-layered epithelia as well as in tumors derived from these cells. In cancers arising from KRT17 negative single layered epithelia neo-expression of KRT17 has been associated with tumor progression. To obtain more insight into the biology of kidney cancers we have investigated KRT17 expression by immunohistochemistry in normal kidney, in papillary preneoplastic lesions and in 151 papillary and 692 conventional renal cell carcinomas placed on tissue microarray. We found a positive staining in ureteric bud and collecting duct cells in foetal kidney, in all papillary preneoplastic lesions and also in 77% of the 151 papillary renal cell tumors indicating a continuos KRT17 expression during tumor development. The neo-expression of KRT17 in conventional renal cell carcinomas, which derives from KRT17 negative proximal tubules showed a significant correlation with postoperative tumor relapse (RR=2.50; 95% CI=1.59-3.94; p<0.001). In conclusion, the continuous expression of KRT17 from emerging fetal kidney tubules and microscopic pre-neoplastic lesions towards papillary renal cell tumors and its neo-expression in aggressive growing conventional renal cell carcinomas reflects the multiple function of KRT17 in kidney cancers with distinct natural history. This should be taken into account in clinical managements and therapy.
Gesehen am 22.10.2019